2015
DOI: 10.3109/0886022x.2015.1024555
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and its correlates in patients with chronic kidney disease: a cross-sectional design

Abstract: Purpose: Since sympathovagal imbalance influences clinical phenomena, such as hypertension, diabetes mellitus, chronic kidney disease (CKD) and sleeping problems, there should be correlations between these conditions. We hypothesized that sleep quality would be correlated with estimated glomerular filtration rate (eGFR), blood pressure and the presence of diabetes. Methods: We included 303 CKD patients in this study. We employed the Pittsburgh Sleep Quality Index (PSQI), Beck Depression Inventory (BDI) and Sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 41 publications
8
31
0
4
Order By: Relevance
“…However, some earlier studies have shown that sleep problems had increased the risk of CVDs, hypertension, diabetes, and obesity, all of which were implicated in the etiology of chronic kidney diseases [43]. More recent studies have indicated sleep problems also among kidney patients [44], [45]. In line with the existing evidence, the present study too showed that all of the sleep problems increased the odds of renal failure.…”
Section: Discussionsupporting
confidence: 88%
“…However, some earlier studies have shown that sleep problems had increased the risk of CVDs, hypertension, diabetes, and obesity, all of which were implicated in the etiology of chronic kidney diseases [43]. More recent studies have indicated sleep problems also among kidney patients [44], [45]. In line with the existing evidence, the present study too showed that all of the sleep problems increased the odds of renal failure.…”
Section: Discussionsupporting
confidence: 88%
“…Upon exclusion of studies that included patients with diabetes mellitus, urinary tract infections, and chronic kidney diseases, the association between poor sleep quality and SBP (mean difference, 3.99; 95% CI, −3.88 to 11.86 [ I 2 = 98%]) or DBP (mean difference, 1.23; 95% CI, −2.28 to 4.74 [ I 2 = 95%]) remained statistically insignificant and highly heterogeneous.…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Elder et al .,[ 5 ] the lower scores on sleep quality were associated with a variety of cardiovascular problems, mental disorders, depression, itching, and pain. Considering that a cold dialysis solution can be effective in improving cardiovascular problems, depression, pain, and itching,[ 9 ] sleep disturbances may be indirectly improved.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that insomnia, sleep deprivation, and general sleep disorders are associated with the exacerbation of cardiovascular diseases, decreased quality of life, and increased mortality in hemodialysis patients. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%